TYPES OF ARTISTIC REFERENCE: PROBLEMS OF INTERPRETATION - Smushchynska, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article is devoted to the problems of artistic reference, the ways of its presentation in the artistic text and the possibilities of understanding. The types of artistic reference characteristic of the modern French novel are analyzed. The conducted analysis allows us to talk about three main types – introductory, identifying, undefined. Besides, attention is focused on the interconnection of the categories of reference and modality, as well as on its representation in different parts of architecture and composition. ______________ References: • Burak, V. Reference in Realistic Prose: An Ethnolinguistic Aspect. Linguistic Studies35 (2018): 93-99. • Burbelo, V. B. Artistic Discourse in the History of French Language and Culture of the 9th-18th Centuries. Doctoral dissertation in Philological Sciences, Kyiv University, 1999. 455 p. • Vorobyova, O. P. Cognitive Poetics: Spectrum of Issues and Research Directions. Philological Studies14 (2020): 11-22. • Lotman, Y. M. Text within the Text. Anthology of World Literary and Critical Thought of the 20th Century (Lviv: Litopys, 1996): 430-441. • Romance Studies of the Early 21st Century: Textual Concepts, Narratives, Possible Worlds. Collective Monograph, O. M. Kaganovska et al. (Kyiv: VTC KSLU, 2012), 223 p. • Sazonova, Y. Y. Types of Reference in Horror Discourse Texts. Linguistic Studies43 (2016): 208-216. • Selivanova, O. Contemporary Linguistics: Terminological Encyclopedia (Poltava: Dovkillya-K, 2006), 716 p. • Selivanova, O. Referent. In Contemporary Linguistics: Terminological Encyclopedia (Poltava: Dovkillya-K, 2006), 514-515. • Smushchynska, I. V. Modality of French Artistic Text: Types and Means of Expression: Abstract of DSc thesis, Kyiv University, 2003. 39 p. • Shkurashivska, L. M. Semantic-Pragmatic Features of Temporal Reference (Based on French Language Material). Bulletin of KhNU 1124 (2014): 104-109. • Shtern, I. B. Selected Topics and Lexicon of Contemporary Linguistics: Encyclopedic Dictionary (Kyiv: ArtEk, 1998), 336 p. • Jakobson, R. Linguistics and Poetics. Anthology of World Literary and Critical Thought of the 20th Century (Lviv: Litopys, 1996): 359-377. • Barthes Le degré zéro de l’écriture suivi de Eléments de sémiologie (P. : éd. Du Seuil, 1972), 182 p. • Donnellan Keith Reference and definite descriptions. The Philosophical Review 75 (3) (1966): 281-304. • Eco Les limites de l’interprétation (P. : Grasset, 1992), 406 p. • Genette Figures III (P. : Editions du Seuil, 1972), 286 p. • Groupe µ. Rhétorique générale (: Editions du Seuil, 1982), 232 p. • Molinié G. Eléments de stylistique française (P.: PUF, 1997), 213 p. • Müller-Freienfels Psychologie der Kunst (Leipzig, Berlin, 1922, 1923). Bd. 1: Allgemeine Grundlegung und Psychologie des Kunstgeniessens. Zweite, vollständig umgearbeitete und vermehrte Auflage (1922); Bd. 2: Psychologie des Kunstschaffens und der Ästhetischen Wertung (1923). • Quine Van O. From a logical point of view. 9 Logico-Philosophical Essays (Cambridge: Harvard University Press, 1953). • Rassell Introduction to Mathematical Philosophy, 2 ed. Ch. XVI: Descriptions (London, 1920): 167-180. • Strawson F. Identifying reference and truth-values. Theoria XXX (1964): 86-99. • Balzac de. La peau de chagrin (M. : Ed. en langues étrangères, 1958), 308 p. • Ernaux Journal du dehors (P. : Gallimard, 2000), 107 p. • Flaubert Salammbô (M. : Progrès, 1978), 453 p. • Hugo Les travailleurs de la mer (M. : Ed. en langues étrangères, 1952), 358 p. • Histoire de Gil Blas de Santillane (Amsterdam : Meulenhoff), 148 p. • Merle Derrière la vitre (M. : Vyssaya skola, 1982), 159 p. • San-Antonio. Le standinge ou le savoir-vivre de Bérurier (: Editions Fleuve noir, 1965), 442 p. • Simenon Le Bourgmestre de Furnes (Bruxelles : Editions Labor, 1983), 203 p. • Simenon Les 13 mystères (P. : Presses Pocket, 1978), 185 p. • Lucien Leuwen (M. : Radouga, 1984), 679 p. • Vian L’arrache-cœur (P. : Ed. J.-J. Pauvert, 1974), 256 p. • Zola La Curée (P. : Garnier-Flammarion, 1970), 315 p.